Access Route for Endovascular Neurointervention - Transfemoral to Transradial: Is it Worth the Effort and are we Ready for the Change? - Ahuja, Chirag Kamal; Agarwal, Vivek; Vyas, Sameer; Gupta, Vivek (Journal of Clinical Interventional Radiology ISVIR, 2021)
Transfemoral access for neurointerventions has been a time-tested technique of entering the vascular network of the body and reaching the intended targets. However, it has its own share of shortcomings in the form of long admission times leading to increased costs, patient inconvenience and local (though infrequent) adverse affects. Transradial route has taken the interventional cardiology domain by storm and is staring now at other vascular domains especially neurointervention. It has shown better outcomes than the transfemoral route in many aspects. The current article discusses the vascular access perspectives with an exhaustive overview of the transradial route concerning its historical perspectives, its requirement in the current clinical scenario, the procedure per se including the adverse effects and whether it has the real world charm to displace the transfemoral route into the backseat. Transradial access in neurointervention is here to stay, however it would require training, certain modifications in the standard catheters that one currently uses for cerebral procedures and constant practice by the operator to cross the learning curve and attain a certain level of competence before he becomes comfortable with the technique.
Keywords: transradial; endovascular; neurointervention; access route